Perancangan Sistem Informasi Akuntansi Penjualan Online Menggunakan Visual Studio Di Gbescoot - Hilda Widi Rahayu; Karyadi Karyadi; Falaah Abdussalaam (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted with the aim of analyzing and designing a Sales Information System at the GBEscoot store. According to the research results that have been obtained by the author, sales at this store are carried out in 3 marketplaces so it is necessary to manually re-record all online sales and count them manually. So that this method is less effective and efficient which causes errors in making sales reports. To minimize these errors, the authors create software engineering for online sales with programming applications with the aim of making it easier to find and obtain information related to sales that occur accurately and efficiently. In this study the authors used a qualitative method with a descriptive approach. The process of collecting data carried out by the author is observation, literature study, and interviews. Microsoft Visual Studio programming language with MySQL as the database used to create this sales information system. The author can conclude that by utilizing the sales information system created, sales data can be inputted and processed quickly and the resulting reports are accurate. Keywords: Sales Accounting Information System, Online, Marketplace and Microsoft Visual Studio.